Determining Gender Differential Item Functioning for Mathematics in Coeducational School Culture - S. Kanageswari Suppiah Shanmugam (Malaysian Journal of Learning and Instruction, 2019)
Purpose - In an attempt to explore item characteristics that behave differently between boys and girls, this comparative study examines gender Differential Item Functioning in a school culture that is noted to be â€˜thrivingâ€™ mathematically.